Application of ectoine in diseases of the skin and mucous membranes - Piotr Kuna; Dominika Ochab-Krupnik; Anna Mościcka; Piotr Łacwik (Alergologia Polska)
Ectoine is an organic chemical compound from the group of amino acids, produced by microorganisms to protect cells and their organelles from the adverse effects of the external environment. It has a wide range of applications in dermatology, allergy, laryngology, and ophthalmology. Additionally, ongoing research shows its potential in pulmonary, gastroenterological, and neurological treatment. Ectoine has been shown to have a protective and moisturizing effect on the skin, making it widely used in both the cosmetic and pharmaceutical industries. It has anti-inflammatory and antioxidant properties, which can support skin protection against damage caused by UVA, UVB, visible and infrared light, environmental pollution, or other potentially harmful factors. Ectoine has also been found to have a beneficial effect on the stability of cell membranes and increases their fluidity. It has been shown to have a positive effect on the stability of DNA helix, increases the temperature resistance of DNA polymerase, and lowers the melting temperature of the double-stranded DNA. In addition it reduces oxidative stress and protects nucleic acids from reactive oxygen forms. Ongoing trials confirming its supportive role in several inflammatory conditions are available, including, but not limited to upper respiratory tract infections, allergic rhinitis, chronic sinusitis, asthma, chronic obstructive pulmonary disease and ocular conditions. It is already available in various practical forms, such as cremes, gels, nasal and pharyngeal sprays and lozenges. The growing body of research suggests further applications, making ectoine a potential key player in supportive treatment of both chronic and acute inflammatory conditions.